1937
DOI: 10.1021/ja01289a003
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Equilibria of Sodium Sulfate at Temperatures from 150 to 350°.1 III. Effect of Sodium Hydroxide and Sodium Phosphate

Abstract: The present paper is the third in a series presenting the results of an investigation carried out in coiiperation with the Joint Research Committee on Boiler Feedwater Studies dealing with the solubility of sodium sulfate in various solutions in the temperature range from 150 to 350". The first paper5 gave solubility data for sodium SUIfate, in sodium hydroxide-sodium chloride solutions, and the secondfi for sodium sulfate in SOdium hydroxide-sodium carbonate solutions. This paper presents data for (1) a desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1947
1947
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…A two-liquid-phase region was also discovered but with a minimum temperature of 360 °C, which was approximately 85 °C higher than that estimated for corresponding Na2HPC4 solutions (2). Substitution of potassium phosphate for sodium phosphate as an additive would therefore prevent the formation of a second liquid phase in the region of steam generator operation (275-325 °C) that otherwise could have caused thinning as proposed by Garnsey (7). This substitution might again make phosphates useful in eliminating particular problems of corrosion (including denting) as suggested earlier (3).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A two-liquid-phase region was also discovered but with a minimum temperature of 360 °C, which was approximately 85 °C higher than that estimated for corresponding Na2HPC4 solutions (2). Substitution of potassium phosphate for sodium phosphate as an additive would therefore prevent the formation of a second liquid phase in the region of steam generator operation (275-325 °C) that otherwise could have caused thinning as proposed by Garnsey (7). This substitution might again make phosphates useful in eliminating particular problems of corrosion (including denting) as suggested earlier (3).…”
Section: Introductionmentioning
confidence: 84%
“…After the discovery by Broadbent et al {2) that aqueous solutions of disodium hydrogen phosphate form two immiscible liquids at temperatures near 300 °C, Garnsey (7) proposed that the resulting concentrated and strongly corrosive solution, possibly produced by boiling concentration, may have corroded the steam generator tubes to cause thinning. Recently, the 0021-9568/82/1727-0175501.25/0 analogous dipotassium hydrogen phosphate-water system has been studied at this laboratory at temperatures from 100 to 400 °C (3), motivated by the earlier work of Broadbent et al (2), by the proposals of Garnsey (7), and by knowledge that at temperatures below 100 °C potassium salts are more soluble than the analogous sodium salts (4,5). This recent work showed that aqueous K2HPC4 solutions at high temperatures still were much more soluble than those of Na2HP04.…”
Section: Introductionmentioning
confidence: 99%
“…E. OPTICAL DATA 1. Properties of pure compounds Ingerson and Morey (60) have recently collected all available optical data on sodium phosphates (8,12,28,65,95,114) and added a few of their own. Their 10 Suggested to the writer by Dr. A. S. Richardson during the course of our studies.…”
Section: Ionic Structurementioning
confidence: 99%
“…The highest temperature at which there are measurements for liquid-phase solubility is 350 °C. The mole-fraction solubihty at that temperature is 1.65 x 10^a ccording to Schroeder et al [28] and 5.97 x 10^a ccording to Wetton [27]. We decided to give more weight to the more recent study [27], since the complex chemistry was not appreciated at the time of the Schroeder et al [28] work.…”
mentioning
confidence: 99%
“…The mole-fraction solubihty at that temperature is 1.65 x 10^a ccording to Schroeder et al [28] and 5.97 x 10^a ccording to Wetton [27]. We decided to give more weight to the more recent study [27], since the complex chemistry was not appreciated at the time of the Schroeder et al [28] work. We therefore used a value of 5.0 x 10^. For the distribution between vapor and liquid, we used the data of Goodstine [29, supplemented by additional data courtesy of ABB Combustion Engineering], who measured the partitioning of sodium between vapor and liquid phases at various concentrations and pressures.…”
mentioning
confidence: 99%